Repeatability and reliability of muscle relaxation properties induced by motor cortical stimulation - Molenaar, J. P.; Voermans, N. C.; de Jong, L. A.; Stegeman, D. F.; Doorduin, J.; van Engelen, B. G. (Journal of applied physiology (1985), 2018)
Impaired muscle relaxation is a feature of many neuromuscular disorders. However, few tests are available to quantify muscle relaxation. Transcranial magnetic stimulation (TMS) of the motor cortex can induce muscle relaxation by abruptly inhibiting corticospinal drive. The aim of our study was to investigate whether repeatability and reliability of TMS-induced relaxation are greater than voluntary relaxation. Furthermore, effects of sex, cooling, and fatigue on muscle relaxation properties were studied. Muscle relaxation of deep finger flexors was assessed in 25 healthy subjects (14 men and 11 women, age 39.1 ± 12.7 and 45.3 ± 8.7 yr, respectively) with handgrip dynamometry. All outcome measures showed greater repeatability and reliability in TMS-induced relaxation compared with voluntary relaxation. The within-subject coefficient of variability of normalized peak relaxation rate was lower in TMS-induced relaxation than in voluntary relaxation (3.0% vs. 19.7% in men and 6.1% vs. 14.3% in women). The repeatability coefficient was lower (1.3 vs. 6.1 s −1 in men and 2.3 vs. 3.1 s −1 in women) and the intraclass correlation coefficient was higher (0.95 vs. 0.53 in men and 0.78 vs. 0.69 in women) for TMS-induced relaxation compared with voluntary relaxation. TMS enabled demonstration of slowing effects of sex, muscle cooling, and muscle fatigue on relaxation properties that voluntary relaxation could not. In conclusion, repeatability and reliability of TMS-induced muscle relaxation were greater compared with voluntary muscle relaxation. TMS-induced muscle relaxation has the potential to be used in clinical practice for diagnostic purposes and therapy effect monitoring in patients with impaired muscle relaxation. NEW & NOTEWORTHY Transcranial magnetic stimulation (TMS)-induced muscle relaxation demonstrates greater repeatability and reliability compared with voluntary relaxation, represented by the ability to demonstrate typical effects of sex, cooling, and fatigue on muscle relaxation properties that were not seen in voluntary relaxation. In clinical practice, TMS-induced muscle relaxation could be used for diagnostic purposes and therapy effect monitoring. Furthermore, fewer subjects will be needed for future studies when using TMS to demonstrate differences in muscle relaxation properties.